Biuret—A Crucial Reaction Intermediate for Understanding Urea Pyrolysis To Form Carbon Nitrides: Crystal‐Structure Elucidation and In Situ Diffractometric, Vibrational and Thermal Characterisation. Issue 63 (7th October 2020) - Gross, Peter; Höppe, Henning A.
Abstract: The crystal structure of biuret was elucidated by means of XRD analysis of single crystals grown through slow evaporation from a solution in ethanol. It crystallises in its own structure type in space group C 2/ c ( a =15.4135(8) Å, b =6.6042(3) Å, c =9.3055(4) Å, Z =8). Biuret decomposition was studied in situ by means of temperature‐programmed powder XRD and FTIR spectroscopy, to identify a co‐crystalline biuret–cyanuric acid phase as a previously unrecognised reaction intermediate. Extensive thermogravimetric studies of varying crucible geometry, heating rate and initial sample mass reveal that the concentration of reactive gases at the interface to the condensed sample residues is a crucial parameter for the prevailing decomposition pathway. Taking these findings into consideration, a study on the optimisation of carbon nitride synthesis from urea on the gram scale, with standard solid‐state laboratory techniques, is presented. Finally, a serendipitously encountered self‐coating of the crucible inner walls by graphite during repeated synthetic cycles, which prove to be highly beneficial for the obtained yields, is reported. Abstract : Down in flames : The pyrolysis of urea and its decomposition products are studied in situ, for the first time. Biuret is a crucial intermediate for decomposition towards g‐C3 N4 . Extensive thermogravimetric studies of varying crucible geometry, heating rate and initial sample mass reveal that the concentration of reactive gases at the interface to the condensed sample residues is a crucial parameter for the prevailing decomposition pathway.